The Future of Digital Research Infrastructure - CROTT, Emma (Institutional Knowledge at Singapore Management University, 2024)
Over the last decade, eResearch has changed from being at the frontier to an underpinning capability required for all research. As digital research infrastructure matures and evolves, we must optimise the delivery of digital services to researchers, reduce duplication of effort across institutions and research domains, and build enduring capability for the research community. The Australian Research Data Commons (ARDC) has responded to this challenge by creating Thematic Research Data Commons to support the maximum number of researchers in strategic priority areas. We’re building data assets, tools and skills that will constitute a national ‘knowledge infrastructure’ that enables Australian researchers to transform our lives. The ARDC has undertaken extensive nation-wide consultations to gain a deep understanding of the research community’s needs. This presentation will describe the data challenges identified and set out the program of work for our first three Research Data Commons: People RDC for health and medical research; Planet RDC for earth and environmental sciences; and HASS and Indigenous RDC for humanities, arts, social sciences, and Indigenous research.